Bapak Rumah Tangga Sebagai Maskulinitas Baru dalam Anime The Way of Househusband Season 1 - Arvy Annora Calluella Gozali (Jurnal Ilmu Komunikasi, 2022)
Representation is an important aspect in society to help society form an expectation of the role of a gender. The roles of each gender will continue to develop and change along with the changing times and how gender is represented in the media. These changes include allowing for the exchange of roles between genders. This is what is trying to be described in the Anime series The Way of Househusband. This research is made to explain how the values of new masculinity and a househusband are represented in the Anime The Way of Househusband. To see the values of new masculinity and the representation of a househusband in The Way of Househusband Anime, a qualitative method is used by analyzing the text using Roland Barthes's semiotic method. The analysis is carried out by interpreting the text denotatively, connotatively, and how the myth behind it is based on Janet Saltzman Chafetz's concept of masculinity. The results of the study state that Tatsu as the main character is able to fulfill five of the seven aspects of masculinity according to Chafetz. Tatsu represents masculinity through his competitive nature, intellectual ability, physical characteristics, steadfastness, and leadership spirit. This indicates that Tatsu, as househusband, still fulfills masculine expectations and forms a new concept of masculinity. Anime The Way of Househusband is able to provide a new representation of masculinity and illustrates that changing gender roles is possible and not terrible.